Association between gut microbiota and common overlapping gastrointestinal disorders: a bidirectional two-sample Mendelian randomization study - Huang, Yuhan; Kang, Zhen; He, Yuhan; Qiu, Yi; Song, Yuhui; Liu, Weiai (Frontiers in Microbiology, 2024)
The main functional gastrointestinal disorders (FGIDs) include functional dyspepsia (FD) and irritable bowel syndrome (IBS), which often present overlapping symptoms with gastroesophageal reflux disease (GERD), posing a challenge for clinical diagnosis and treatment. The gut microbiota is closely associated with FGIDs and GERD, although the causal relationship has not been fully elucidated. Therefore, we aim to investigate the potential causal relationship using bidirectional two-sample Mendelian randomization (MR) analysis.The genetic data of the 211 gut microbiota were obtained from the MiBioGen consortium (N = 14,306, from phylum to genus level) and species level of gut microbiota were acquired from the Dutch Microbiome Project (N = 7738). For FD and IBS, we utilized the Finngen consortium, while for GERD data analysis, we obtained the IEU OpenGWAS project. Inverse-variance weighted (IVW) is used as the primary method to calculate causal effect values. Sensitivity analyses were also performed to confirm the robustness of the primary findings of the MR analyses. Moreover, a reverse MR analysis was conducted to assess the likelihood of reverse causality.Combining the results of the preliminary and sensitivity analyses, we identified 8 that gut microbial taxa were associated with FD. Genus Lachnospiraceae NK4A136 group (P = 3.63 × 10 -3 ), and genus Terrisporobacter (P = 1.13 × 10 -3 ) were strongly associated with FD. At the same time, we found that 8 gut microbial taxa were associated with IBS. Family Prevotellaceae (P = 2.44 × 10 -3 ) and species Clostridium leptum (P = 7.68 × 10 -3 ) display a robust correlation with IBS. In addition, 5 gut microbial taxa associated with GERD using the IVW approach. In reverse MR analysis, 2 gut microbial taxa were found to be associated with FD, 5 gut microbial taxa were found to be associated with IBS, and 21 gut microbial taxa were found to be associated with GERD.The study reveals the potential causal effects of specific microbial taxa on FD, IBS, and GERD, and may offer novel insights into the diagnosis and treatment of these conditions.